PARENTAL INVOLVEMENT IN EDUCATIONAL ACTIVITIES OF CHILDREN IN TEA GARDEN COMMUNITY - SPECIAL REFERENCE TO DIBRUGARH DISTRICT KHOWANG DEVELOPMENTAL BLOCK - Koiri, Punam; Ali, Lokman; Hernwal, Dharam Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s world, parents prioritize their children’s education, believing it’s the key to a successful future. They actively participate children’s educational journey learning journey, hoping to ensure children achieve a good social standing later in life. This study explored the effects of parental involvement on children’s academic performance within tea communities. Specifically, it examined two aspects of parental involvement: participation in various curriculum and related activities and c0-curriculum activities also home engagement in home-based activities -based academic support. This study also investigated the challenges faced by parents when they trying to support their children education. The research focused on 100 parents of children attending a lower primary school in the tea gardens of the Khowang developmental block in Dibrugarh district, Assam. Participants were randomly selected, and data was collected using interviews and questionnaires. This research aims to understand how parental involvement influences academic outcomes and to identify potential barriers that hinder parental support in these communities. Further research could explore specific strategies parents use to support their children’s learning, the impact of socioeconomic factors on parental involvement, and the collaboration between parent’s involvement and student’s motivation level.